2014
DOI: 10.3109/14767058.2014.899574
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of obstetric Doppler ultrasound in fetuses with fetal growth restriction: an observational study in a tertiary care hospital

Abstract: There is a prognostic value of UAD in predicting the outcomes for FGR fetuses and therefore recommend its use in the conservative management of such pregnancies to reduce perinatal mortality and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Despite earlier timing of delivery, AREDF did not lead to an increase in the adverse composite neonatal outcome, compared with the PEDF group. A previously published retrospective study 20 also showed that delivery occurred earlier in the AREDF group and that more cesarean sections were performed in this group, compared with the PEDF group. Also, studies conducted earlier with a comparable study population 15,21,22 reported intraventricular hemorrhage rates of 2–4%, which is similar to our findings.…”
Section: Discussionsupporting
confidence: 55%
“…Despite earlier timing of delivery, AREDF did not lead to an increase in the adverse composite neonatal outcome, compared with the PEDF group. A previously published retrospective study 20 also showed that delivery occurred earlier in the AREDF group and that more cesarean sections were performed in this group, compared with the PEDF group. Also, studies conducted earlier with a comparable study population 15,21,22 reported intraventricular hemorrhage rates of 2–4%, which is similar to our findings.…”
Section: Discussionsupporting
confidence: 55%
“…Artery. It is well documented that amongst those with FGR, abnormal umbilical artery duplex Doppler velocimetry may be associated with adverse perinatal outcome [37,38]. One well-documented Doppler abnormality that is very predictive of abnormal perinatal outcome is reversed enddiastolic umbilical artery flow.…”
Section: Us Duplex Doppler Velocimetry Fetal Umbilicalmentioning
confidence: 99%
“…Therefore its use is recommended to reduce perinatal mortality and morbidity. 11 This study was done to analyze the role of Obstetric Doppler Velocimetry studies in predicting mode of delivery and perinatal outcome.…”
Section: Introductionmentioning
confidence: 99%